2010
DOI: 10.1590/s0074-02762010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemica characterisation of endoplasmic reticulum α 1,2-mannosidase from Sporothrix schenckiil

Abstract: N-glycosylation of proteins is a common post-translational modification in eukaryotic cells. Following the translocation of nascent proteins into the endoplasmic reticulum (ER), the Glc 3 Man 9 GlcNAc 2 oligosaccharide is transferred to asparagine residues and sequentially processed by ER α-glucosidases, which remove the three glucose residues and by α-mannosidases that trim at least one mannose residue (Kornfeld & Kornfeld 1985, Herscovics 1999a.Alpha-mannosidases are grouped within families 38 and 47 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…The genomes of S. schenckii and S. brasiliensis contained the orthologs involved in elaboration of the N -linked glycan core, its transference to proteins and in early trimming. These genes are also known to be involved in glycoprotein endoplasmic reticulum-associated degradation, a quality control system for proteins synthesized within the secretory pathway [9092] (Additional file 2: Table S11). Furthermore, the genomes contain the putative orthologs encoding Golgi-resident glycosidases and glycosyltransferases that further modify N -linked glycans, generating both hybrid and complex N -linked glycans.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of S. schenckii and S. brasiliensis contained the orthologs involved in elaboration of the N -linked glycan core, its transference to proteins and in early trimming. These genes are also known to be involved in glycoprotein endoplasmic reticulum-associated degradation, a quality control system for proteins synthesized within the secretory pathway [9092] (Additional file 2: Table S11). Furthermore, the genomes contain the putative orthologs encoding Golgi-resident glycosidases and glycosyltransferases that further modify N -linked glycans, generating both hybrid and complex N -linked glycans.…”
Section: Resultsmentioning
confidence: 99%
“…Mendes et al (2011) reported a frequency of 36.1% of LAM among 93 isolates from the metropolitan São Paulo area, and Gomes et al (2011), who provided the first insight into the population structure of TB isolates in Brazil, reported that the lowest percentage of the LAM lineage (35.0%) had been observed among 180 isolates from São Paulo state. Noguti et al (2010) showed the lowest percentage (34.7%) of this lineage in Maringá (93 isolates), and Miranda et al (2011) showed the highest percentage (55.3%) of this lineage in Minas Gerais (114 isolates).…”
Section: Discussionmentioning
confidence: 98%
“…Cells were washed twice with deionized water and mechanical disrupted in a Braun homogenizer, with 16 cycles of 30 s and cooling on ice in-between (Mora-Montes et al, 2010b). Cell walls were pelleted by centrifuging and cleaned with sequential incubations with hot 2% (v/v) SDS (BioRad), 0.3 M β-mercaptoethanol (Sigma), and 1 M NaCl (Sigma), as described (Mora-Montes et al, 2007).…”
Section: Methodsmentioning
confidence: 99%